Pembuatan Sistem Informasi Sekolah Berbasis Website pada Sekolah Dasar Negeri 6 Masbagik Selatan - Yahya, Yahya; Baiq Rizki Hidayati; Muhammad Zainul Ardi; Siti Ayu Luffiyati Hamid; Eka Julianti5, Rahmatul Fajri; Rahmatul Fajri (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The rapid development of information technology has a significant impact on various sectors, including education. To implement information technology, one of them is to create a website-based school information system. The Website-based School Information System aims to support the process of delivering information quickly and accurately. The activity of creating a website-based information system at Elementary School (SDN) 6 Masbagik Selatan was created because there was no website-based information system. This website is designed using the PHP programming language and is supported by XAMPP as a local server, with the following targets: introducing the school profile, conveying the latest information, and promoting the school and its activities widely to the community, so that the existence of SDN 6 Masbagik Selatan can be known in its entirety. This system includes various features such as the home page, school history, teacher list, student list, announcements, and activity gallery. Through this system, SDN 6 Masbagik Selatan can provide more transparent and efficient information services to the community. This system has been completed with Online status and can be accessed by the wider community, so that the community is satisfied, especially the school consisting of school management, staff and teachers of SDN 6 Masbagik Selatan. In addition, this website has also strengthened the relationship between the school and parents of students, as well as supporting the promotion of the school widely.